Die soziale Differenzierung der Agrar-Landschaft im Rhein-Main-Gebiet - Hartke, Wolfgang (ERDKUNDE, 1953)
Using examples taken from the Rhine-Main area, this paper shows that the regional differentiation of the highly developed cultural landscapes of Middle Europe is very largely due to social causes. Even degree and extent of these differences appear to depend on social factors, although physical factors are of varying importance in the shaping of the landscape. Physiognomically uniform phenomena are often the result of different sets of underlying factors, particularly in areas which are experiencing social and economic change. In order to evaluate correctly statistical data which superficially appear to be the same it is necessary to map the single units making up the Landschaftsgefüge (regional structure) according to the status and social class of the owners of land. Statistical data on a parish basis are insufficient for this purpose; mapping of the social conditions as suggested enables evolution series to be established for each sub-unit of the region, and assists the discovery of signs of crisis in the landscape, such as the „Sozialbrache (land undeveloped because of social factors). These evolution series can serve as a basis for planning. The simple land-use survey which does not take into account the relationship of each unit of a region to certain social groups is not suitable for that purpose.